SUSTAINABLE TOURISM DESTINATION MARKETING STRATEGY IN THE DIGITAL ERA - Sukardi, Ni Wayan; Dasih, I Gusti Ayu Ratna Pramesti (International Journal of Social Science, 2025)
Tourism destination marketing plays a very crucial role in increasing the number of tourist visits. In this fast-paced digital era, effective promotion is the key to attracting domestic and international tourists. Thus, every tourist destination needs the right marketing strategy to compete in the increasingly competitive global market. The development of digital technology has had a significant impact on tourism destination marketing strategies, especially in the context of sustainable tourism. This research aims to identify effective marketing strategies in promoting tourist destinations as sustainable tourism destinations in the digital era. This research uses a descriptive quantitative approach by utilizing data from interviews and various sources. The research results show that digital marketing is essential in tourism marketing. Social media, websites, and other digital platforms are critical in increasing tourist attraction. Besides that, collaborating with various parties, including the government, local communities, and business actors, supports tourism sustainability. Hopefully, these findings can provide a clearer picture of marketing strategies that can be implemented in developing sustainable tourism destinations in digital era. .